2014
DOI: 10.1111/sum.12149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basin‐based conservation agriculture on selected soil quality parameters under smallholder farming inZimbabwe

Abstract: The research was carried out to determine the effect of basin‐based conservation agriculture (CA) on selected soil quality parameters. Paired plots (0.01 ha) of CA and conventional tillage based on the animal‐drawn mouldboard plough (CONV) were established between 2004 and 2007 on farm fields on soils with either low (12–18% – sandy loams and sandy clay loams) or high clay levels (>18–46% – sandy clays and clays) as part of an ongoing project promoting CA in six districts in the smallholder farming areas of Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…The three studies found that effects on soil carbon are dependent on the quality of CA implementation, such as the type of seeding system, the level of diversification, the type of rotation systems used, the amount of biomass that could be retained, and the inclusion of tree-based elements. Different CA systems often had sitespecific responses, making it difficult to draw general conclusions (Nyamangara et al , 2014aThierfelder et al 2016a;Mupangwa et al 2016a;Thierfelder et al 2015a, b;Baudron et al 2012b). Most studies agree there are yield benefits in the medium to long term which are more pronounced in lower rainfall environments (Pittelkow et al 2015;Thierfelder et al 2014;Steward et al 2018).…”
Section: Rationale Of Conservation Agriculturementioning
confidence: 99%
“…The three studies found that effects on soil carbon are dependent on the quality of CA implementation, such as the type of seeding system, the level of diversification, the type of rotation systems used, the amount of biomass that could be retained, and the inclusion of tree-based elements. Different CA systems often had sitespecific responses, making it difficult to draw general conclusions (Nyamangara et al , 2014aThierfelder et al 2016a;Mupangwa et al 2016a;Thierfelder et al 2015a, b;Baudron et al 2012b). Most studies agree there are yield benefits in the medium to long term which are more pronounced in lower rainfall environments (Pittelkow et al 2015;Thierfelder et al 2014;Steward et al 2018).…”
Section: Rationale Of Conservation Agriculturementioning
confidence: 99%
“…4). Conservation tillage methods such as ripping have been reported to result in high pore volumes consequently increasing the infiltration capacity of a soil (Nyamangara et al, 2014) thus reduced water stress. The increased infiltration observed with ripping and mulching may also explain why there was least risk of crop failure (0-30%) under ripper + mulch across the different planting date scenarios and across fertility treatments.…”
Section: Tillage and Mulch Application Effects On Maize Yieldsmentioning
confidence: 99%
“…NT is considered to be a sustainable agricultural system that responds satisfactorily under both economic and environmental pressures (Reicosky & Saxton, ; Araya et al ., ). This agricultural production system uses a body of soil and biomass management practices that produce satisfactory results with respect to controlling erosion in tropical mountains (Pansak et al ., ) and at the same time improve soil quality, by increasing the content of organic matter and improving porosity, structural stability, infiltration and water retention (Carr et al ., ; Nyamangara et al ., ; Chowdhury et al ., ).…”
Section: Introductionmentioning
confidence: 99%